Production and storage of N-enriched co-compost - Adamtey, Noah; Cofie, Olufunke O.; Ofosu-Budu, G.K.; Danso, S.K.A.; Forster, D. (Elsevier, 2009)
Recovery of the organic fraction of municipal waste for peri-urban agriculture could contribute to the improvement of environmental sanitation and increase agricultural productivity in Sub-Saharan Africa. However, municipal waste co-compost (Co) has low nitrogen (N) content. Therefore, this study investigated the type and form of inorganic N fertiliser that is capable of improving the nitrogen content of Co and monitored the changes in the properties of this N-enriched product under storage. To attain 30,000 mg kg1 (3%) N content, different amounts of urea or ammonium sulphate were applied in various forms (dry, paste and liquid) to enrich Co. The product termed comlizer was stored and its moisture, pH, total nitrogen, NH2?4 -N, NO3 -N, and C/N ratio were monitored under ambient conditions for two years. In the first four months of storage, total N content of 50 kg Co + 3.26 kg urea (CoUD) increased from 31,333 to 54,000 mg kg1, and 50 kg Co + 7.14 kg (NH4)2SO4 (CoASD) from 35,333 to 52,000 mg kg1. At the end of two years of storage, the initial N content of CoUD and CoASD decreased by 47% and 24%, respectively. Based on these results, it is recommended that dry (NH4)2SO4 should be used in N enrichment of Co, and that the comlizer should be stored in sealed bags but not more than four months.